Cognitive Learning and Teaching Style - Yahaya, Azizi (2008)
Cognitive teaching and learning styles encourage the development of our country in all different attachment. Cognitive load theory adopts an appropriate approach to the efficient and effective teaching of defined content. The packaged computer based learning environments are highly effective, controlled that filter out much of the world’s complexity and provide learners with an authentic enough environment conducive to learning. The problem-based learning model is simpler in design yet more ambitious in the sense that it departs more radically from established instructional methods. At the same time, some of the most valuable lesson , may learned many come from the real – world experience gained in setting up and administering program. The implementation can be just as important as the theory guided design. The constructivist movement in education involves curriculum reform a rethinking of what if means to know something. Teachers and students must see the sense of what they are doing, come to believe in the efficacy of the program and work hard to ensure that the right outcomes are achieved.